KESADARAN HUKUM MASYARAKAT TERHADAP PROTOKOL KESEHATAN DALAM MASA PANDEMI COVID-19 DI KOTA DENPASAR - Sudarma Putra Ida Bagus (Jurusan Hukum Fakultas Dharma Duta Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2022)
The COVID-19 pandemic has had a huge impact not only on medical or epidemiological matters, but also on constitutional matters that affect all joints of state and people's lives, especially in Indonesia. Various policies were issued by the central government during this pandemic, namely in the fields of health, economy, social affairs, and education by focusing on accelerating handling and reducing the rate of spread of COVID-19, one of which is by increasing legal awareness in complying with health protocols. The central government's policy produces products of the rule of law that are followed and implemented thoroughly by every province, regency and city in Indonesia, and as a form of application of the principle of decentralization and deconcentration, one of which is the city of Denpasar, Based on data from Bali Province until March 2021, Denpasar city is the highest contributor to covid-19 cases with 10,976 confirmed cases with details of 787 in treatment, 9,981 recovered, and 208 died. So from the data we see that the high activity carried out by the people of Denpasar city, which is the capital of Bali province, is not followed by the high legal awareness of the people of Denpasar city to comply with health protocols, as an effort to prevent and control COVID-19. Even though the Denpasar city government has also issued Mayor Regulation Number 48 of 2020 concerning the Implementation of Discipline and Enforcement of Health Protocol Law as an Effort to Prevent and Control Corona Virus Disease 2019 (COVID-19) in the New Era Life Order. Based on the background mentioned above, the issues to be discussed can be formulated as follows: 1.What are the factors that affect the level of public legal awareness in complying with health protocols during the COVID-19 pandemic in the city of Denpasar? 2.What are the obstacles and efforts made in raising public legal awareness in complying with health protocols during the COVID-19 pandemic in the city of Denpasar?, using the concept: Legal awareness, COVID-19 Pandemic, COVID-19 Pandemic Health Protocol, using Lawrence M. Friedman's Legal System Theory and Legal awareness, as for the type of research used is empirical legal research, the nature of the research, is descriptive research, The type of data is qualitative and the data source is primary data and secondary data, using data collection methods, obsenvation, interviews, and literature. Informant determination technique using Non probability sampling, the instrument used is mobile phone, the management and analysis of data is qualitative and systematic descriptive. The results of the research obtained are1) factors that affect the level of public legal awareness in complying with health protocols during the COVID-19 pandemic in the city of Denpasar can be seen from the substance of the law (laws and regulations), legal structure (law enforcement and infrastructure), legal culture (community and culture). 2) The biggest obstacle is still from the legal culture factor, namely public legal awareness, in this case there is still a denpasar city community that violates in carrying out health protocols, 3) Efforts that are the Denpasar city government carrying out preventive efforts include prevention carried out by providing encouragement, socialization, and development that is gradual, sustainable, and massive from the village, village, customary village, and banjar levels to increase the participation and legal awareness of individuals, business actors, managers, organizers, persons in charge of public places and facilities and repressive efforts in the form of law enforcement through the implementation of administrative sanctions and sanctions Social in place